2018
DOI: 10.1007/s10843-018-0239-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role of Individual Level and Firm Level Dynamic Capabilities in SMEs’ Internationalization

Abstract: This paper presents a multi-level model that examines the impact of dynamic capabilities on the internationalization of SMEs while taking into account the interactions among them. The purpose of the research is to understand the applicability of dynamic capabilities at the individual and the firm level to the SME internationalization process in developing country context and to assess to what extent a firm's asset position and individual level dynamic capabilities influence the generation of firm level dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 152 publications
2
43
0
12
Order By: Relevance
“…It was found that both EO and EC had a positive relationship with internationalization according to the research of many scholars (e.g., Deligianni et al 2015). In research carried out in Sri Lanka by Mudalige, Ismail and Malek (2019) established that EO and social capital have a positive influence on SME internationalization.…”
Section: Literature Reviewmentioning
confidence: 98%
“…It was found that both EO and EC had a positive relationship with internationalization according to the research of many scholars (e.g., Deligianni et al 2015). In research carried out in Sri Lanka by Mudalige, Ismail and Malek (2019) established that EO and social capital have a positive influence on SME internationalization.…”
Section: Literature Reviewmentioning
confidence: 98%
“…to increase assets firms' assets (Javalgi and Todd, 2011). A number of studies suggest that internationalisation has a positive impact on the growth of a firm's assets (Mudalige et al, 2019;Ling-yee and Ogunmokun, 2001;Chelliah et al, 2010). However, authors such as Hoang (1998), Wolff and Pett (2000) and Shoham et al (2002) did not find any positive impact.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…In conditions involving dynamic and fast-changing environments, DCV explains firm competitiveness more effectively than RBV (Lin & Wu, 2014). Mudalige et al (2019) conceptualise these are organisational dynamic capabilities and institutional dynamic capabilities. Such a perspective implies that both the firm's internal resources external resources must be strategically exploited to create competitive advantage.…”
Section: Resource-based Theory and Dynamic Capabilitiesmentioning
confidence: 99%
“…For this purpose, the operationalization based on one-dimensional indicators, which despite its limitations is successfully applied in research practice e.g., (Pervan, Curak, & Pavic Kramaric, 2018), was used. Results of many studies so far have con irmed a positive impact of dynamic capabilities on the performance and scope of SMEs' market activity (Mudalige, 2015;Rice, Liao, Galvin, & Martin, 2015), on the level of SMEs' internal and open innovation (Nolsøe Grünbaum & Stenger, 2013;Grimaldi, Quinto, & Rippa, 2013;Ripain, Amirul, & Mail, 2017), as well as on SMEs' proactive posture and capability to integrate resources in recognising new opportunities in an environment characterized by high volatility and uncertainty (Battisti & Deakins, 2017;Halim, Adnan, & Khusaini, 2017). An important contribution to the development of the theory and practice of dynamic capabilities was also made by studies conducted by Polish authors.…”
Section: Literature Reviewmentioning
confidence: 99%